Clinical researchEffect of ligamenta flava hypertrophy on lumbar disc herniation with contralateral symptoms and signs: a clinical and morphometric study - Karabekir, Hamit Selim; YIldIzhan, Ahmet; Atar, Elmas K.; YaycIoglu, Soner; Gocmen-Mas, Nuket; Yazici, Canan (Archives of Medical Science, 2010)
Introduction: The purpose of this study was to determine whether ligamentum flavum hypertrophy among disc herniated patients causes contralateral pain symptoms. For this reason we measured the thickness of the ligament in disc herniated patients with ipsilateral or contralateral symptoms. Material and methods: Two hundred disc herniated patients with ipsilateral symptoms as group I were compared with five disc herniated patients with only contralateral symptoms as group II. Ligamenta flava thicknesses and spinal canal diameters of both groups were measured on magnetic resonance imaging (MRI) with a micro-caliper. Results: Both groups underwent surgery only on the disc herniated side. The total thicknesses of the ligamenta flava in group II was thicker than in group I. There was no spinal stenosis in either group and no significance difference between the groups. Statistically significant differences were found for both ipsilateral and contralateral thickness of the ligament flava in both groups. We also compared thickness of the ligamenta flava for each level of disc herniation in group I; ligamenta flava hypertrophy was more common at L3-L4 and L4-L5 levels of vertebrae in females. Conclusions: Aetiology of contralateral sciatica among disc herniated patients may be related to hypertrophy of the ligamenta flava, especially on the opposite side. Surgical approaches of the disc herniated side alone may be sufficient for a good outcome.